Urban and Rural Dietary Patterns in Greece in the Years 1957-2008; An Economic Analysis - Gikas, Grigorios; Georgakopoulos, Georgios; Hyz, Alina; Sotiropoulos, Ioannis; Vasileiou, Konstantinos (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
This paper attempts to describe and study in detail the evolution of urban and rural dietary patterns in Greece during the period 1957-2008, in terms of natural and technical features. Natural features refer to the consumption of animal versus plant products, while technical features pertain to agricultural and industrial products consumption. The analysis leads to a conclusion that the dietary patterns obtain internationalized, industrial origin and growing share of animal products, while the weight of tradition (i.e. Mediterranean plant products and services) weakens in Greece after World War II. Additionally, during this period the urban and rural dietary patterns, by comparison, have evolved at different paces and characteristics; the rural dietary patterns converged to urban ones with ‘asymmetric’ way, time lag and significant particularities.